The main legal and political issues on the continuity of the Republic of Lithuania - Žalimas, Dainius (Politologija, 2000)
This year marks the 10th anniversary of the restoration of the independence of the Republic of Lithuania. Therefore, this article deals with the main legal and political issues on the continuity of Lithuania. Firstly, it focuses on the legal evaluation of the Molotov-Ribbentrop Pact and one of its consequences, the occupation and annexation of Lithuania in 1940. This issue is crucial because it determines the further legal assessment of the restoration of independence of the Republic of Lithuania. The author reminds that from the standpoint of international law Lithuania’s occupation and annexation should be regarded as international crime because the main principles and norms of international law such as the non-use of force, respect to sovereignty, non-interference in the domestic affairs of other states and the self-determination of all nations had been violated by the former USSR. Such a qualification may be supported by the state practice and principles of the Nuremberg War Crimes Tribunal. The Tribunal decided that the serious violations of Article 10 of the Statute of the League of Nations and of Article 1 of the 1928 Paris Treaty made by Germany in 1938-1941 were international crimes. There are no reasons to treat the analogous actions of the Soviet Union in 1940 in a different way. The author goes on that according to the principle ex injuria non oritur jus, no legal benefit can be derived from an illegal act. Therefore, the Soviet Union had not ever obtained any sovereign rights over Lithuania’s territory, i.e. Lithuania had never been a legitimate part of the USSR. Thus it cannot be regarded as one of the former Soviet republics and a successor State of the USSR. Despite the occupation, Lithuania continued to exist as a subject of international law. This continuity was recognized by the major Western powers and other democratic states and was maintained by the Lithuanian legations in foreign states. Therefore, it is only logical that on March 11, 1990 the restoration of the independence of the Republic of Lithuania was enacted on the basis of the de jure continuity of the State. On this basis the current Republic of Lithuania is considered to be identical with the pre-war Republic of Lithuania. Such identity of the Republic of Lithuania has been generally recognized. For instance, on February 11, 1991 Iceland became the first foreign country to recognize the restoration of Lithuania’s independence confirming that the recognition of the independence of the Republic of Lithuania granted by the Government of Iceland in 1922 was still fully in force. Therefore, the recognition of the restoration of the independence of the Republic of Lithuania means the recognition of the new Lithuanian Government rather than of the State. Finally, the author points out that the fact of the illegal occupation and annexation of the Republic of Lithuania and the restoration of Lithuania’s independence on the basis of the de jure continuity of the State was also recognized by Russia in its July 29, 1991 bilateral Treaty on the Fundamentals of Interstate Relations with Lithuania. The opposite position declared by some Russian officials is legally ill-founded and it contradicts this Treaty and other norms of international law. Therefore, the author makes the conclusion that Russia is unable to treat Lithuania as one of the former Soviet republics as well as to hamper Lithuania’s integration into NATO on that ground.